Studies on St Athanasius of Alexandria in Bulgaria 20th and early 21st Century (Forum Theologicum Sardicense, 2025)
Angel Petkov, Studies on St Athanasius of Alexandria in Bulgaria 20th and early 21st Century. Studies on St. Athanasius in Bulgaria during the 20th and 21st centuries are quite limited. This scarcity is due to two main factors. The first is the schism of 1872 and the subsequent isolation of the Bulgarian Exarchate. Studies on St. Athanasius during this period are primarily focused on his life and works, with little emphasis on his teachings. The most significant study of St. Athanasius from this time was written by the Russian Arch-priest George Shavelski. The second factor was the communist regime in Bulgaria (1949–1990), which severely restricted the work of Bulgarian theologians. In 1945, the schism was lifted, and the Patriarch of Constantinople recognized the autocephaly of the Bulgarian Church. The most notable research of this period was conducted by Elijah Tsonevski and Totju Koev. In 1973, to mark the anniversary of the saint’s death, two issues of Duhovna kultura (“Spiritual Culture”) were dedicated to him. These issues included papers by Tsonevski, Koev, Boyan Piperov, Todor Poptodorov, Ivan Panchovski, and Todor Subev.After the fall of the communist regime in 1989, interest in the Church Fathers grew, and conditions for the study of theology improved. In this new era, Stoyan Chilikov and Svetoslav Ribolov contributed new studies offering different perspectives on the theological priorities of St. Athanasius. There is also a study by Anna Tsvetkova-Glaser, a Roman Catholic. Protestant authors have also contributed to research on St. Athanasius by translating the works of Tommy Lane and Millard Erickson, who provide valuable information about the saint's life, work, and teachings.
Keywords: Saint Atanasius; Bulgarian Exarchate; Catholicity; Church Fathers; Patrology; Dogmatic; Theology